Construct validity and internal consistency of the Brazilian version of Leisure Attitude Measurement for the elderly - Vivian Carla de Castro; Cremilde Aparecida Trindade Radovanovic; Mara Solange Gomes Dellaroza; Bruno Pedroso; Eraldo Schunk Silva; Lígia Carreira (SciELO, 2021)
ABSTRACT Objective: To evaluate the construct validity and internal consistency of the Brazilian version of Leisure Attitude Measurement for the elderly. Method: Methodological study with a quantitative approach. The data were collected for three months through domiciliary visits to a random and representative sample of 384 elders. The internal consistency was measured through Cronbach alpha coefficient. Construct validity was evaluated through exploratory factor analysis. Factor extraction was conducted per principal components, following the Kaiser criterion, with rotation through Varimax solution. Results: The participants' mean age was 70,9 and they were mostly women, married, living with relatives, with one to four years of education, and with an income of up to one minimum wage. The final model of the instrument has conserved three factors, under the parsimony criterion, explaining 50% of data variance, with a total of 27 items distributed across the cognitive, affective, and behavioral domains, with an overall Cronbach alpha coefficient of 0.89. Conclusion: The proposed structural model has shown construct validity and an appropriate internal consistency, explaining 50% of data variability. Its application can promote the understanding of social reality and encourage a positive attitude and elderly engagement in leisure activities.